Dielectric, Ferroelectric, and Piezoelectric Properties of BiFeO3–BaTiO3 Ceramics. Issue 10 (12th July 2013) - Wei, Yongxing; Wang, Xiaotao; Zhu, Jintao; Wang, Xiaoli; Jia, Jiangjiang; Damjanovic, D.
<x xml:space="preserve">Abstract</x> Perovskite solid solution ceramics of (1 − x)BiFeO3–xBaTiO3 (1 − x)BF–xBT, 0.2 ≤ x ≤ 0.45) with high electrical resistivity were prepared by solid‐state reaction method. Actual ferroelectric hysteresis loops and temperature dependence of dielectric constant of the ceramics were obtained. Ceramics of 0.7BF–0.3BT with small rhombohedral distortion show highest remnant polarization (Pr = 26.0 μC/cm2) and piezoelectric coefficient (d33 = 134 pC/N). Compositions with pseudo‐cubic symmetry (intermediate phases) show relaxor‐like dielectric anomaly. The values of Pr and d33 decrease with increasing BT content, from 24.8 μC/cm2 and 104 pC/N for 0.65BF–0.35BT to 8.2 μC/cm2 and 5 pC/N for 0.55BF–0.45BT.